Spanish Adaptation and Validation of the Outcome Questionnaire OQ-30.2 - Errázuriz, Paula; Opazo, Sebastián; Behn, Alex; Silva, Oscar; Gloger, Sergio (Frontiers in Psychology, 2017)
This study describes the psychometric properties of a Spanish version of the Shortened Outcome Questionnaire (OQ-30.2, Lambert et al., 2004), made for the Chilean population. The questionnaire was administered to 546 patients in an outpatient mental health clinic and 100 non-clinical adults. Results indicated that the Chilean version of the measure has good internal consistency (α=0.90) and sensitivity to change. Furthermore, results were similar to those obtained in its original version, making possible its use in the Chilean context.